Issue Information Vol 5 No 2 (2023) - Administrator (Jurnal Kedokteran Gigi Terpadu, 2023)
Jurnal Kedokteran Gigi Terpadu publishes articles and scientific work from Researches, Case Reports and Literature Reviews in Dentistry and Dental Science. The scopes vary from: Dental Surgery, Dental Forensics, Oral Biology, Oral Medicine, Dental Public Health and Preventive Dentistry, Paediatric Dentistry, Dental Materials and Technology, Conservative Dentistry,Orthodontics,Periodontics,Prosthodontics,Dental Radiology.